2002
DOI: 10.1121/1.4778206
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the velocity of a moving object submerged in an ocean waveguide with active sonar

Abstract: Standard active sonar and radar systems are often used to estimate the velocity of a moving target in free space by resolving the Doppler shift of the scattered waveform. In an ocean waveguide, multimodal propagation and dispersion make the Doppler effects far more complicated than in free space. In a waveguide, multiple frequency components are typically present in the field scattered from a moving object even if the active source of radiation is harmonic. Applying a free space Doppler correction to the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…10log 10 of the expected square magnitude of the ambiguity function, based on evaluating Eqs. (14)(15) and (6) is also shown (gray line) and is found to be in good agreement with the Monte-Carlo result. The variance of the ambiguity function dominates the total intensity and the magnitude squared of the ambiguity function's expected value is negligible.…”
Section: Illustrative Examplessupporting
confidence: 82%
See 1 more Smart Citation
“…10log 10 of the expected square magnitude of the ambiguity function, based on evaluating Eqs. (14)(15) and (6) is also shown (gray line) and is found to be in good agreement with the Monte-Carlo result. The variance of the ambiguity function dominates the total intensity and the magnitude squared of the ambiguity function's expected value is negligible.…”
Section: Illustrative Examplessupporting
confidence: 82%
“…For active sensing of a single deterministic target in a waveguide where N 2 Doppler shifts occur, it has been shown that a relatively accurate estimate of the target velocity can be obtained from the Dopplershifted spectrum of its scattered field. 14,15 Here, we show that, for a group of random targets within a resolution cell, accurate simultaneous estimates can be obtained for the instantaneous velocity and position means of the group, as well as their standard deviations through the Moment Method. In Sec.…”
Section: Introductionmentioning
confidence: 99%